Indonesian Adaptation of The International Physical Activity Questionnaire (IPAQ): Psychometric Properties - Dharmansyah, Dhika; Budiana, Dian (Universitas Pendidikan Indonesia, 2021)
ABSTRACTIntroduction: The International Physical Activity Questionnaire (IPAQ) was created to assess physical activity in the community. Objective: This study aims to explore the use of IPAQ in Indonesia with a psychometric approach and cross-cultural adaptation of Indonesia. Methods: Stages of Psychological Evaluation The IPAQ questionnaire began with translating the questionnaire from English to Indonesian, construct assessment by expert judgment, and statistical measurements were carried out to determine the validity and reliability tests. The questionnaire was tested on 25 respondents. Results: The Indonesian version of the IPAQ has a satisfactory criterion validity. A total of 7 question items in the IPAQ were valid. The Kaiser-Meyer-Olkin value was 0.910, and Bartlett's test of sphericity was X2 = 573,434 (df=28, p0.000). Discussion: The Indonesian version of IPAQ is valid and reliable as a measuring tool for physical activity in Indonesian people.Â ABSTRAKPendahuluan: Kuesioner Aktivitas Fisik Internasional (IPAQ) dikembangkan untuk mengukur aktivitas fisik masyarakat. Tujuan: Penelitian ini bertujuan untuk mengeksplorasi penggunaan IPAQ di Indonesia dengan pendekatan psikometri dan cross cultural adaptasi Indonesia. Metode: Tahapan Evaluasi Psikomentri Kuesioner IPAQ dimulai dengan penerjemahan kuesioner dari Bahasa Inggris ke Bahasa Indonesia, penilaian konstruk oleh Â expert judgement, serta dilakukan pengukuran statistkc untuk mengetahui uji validitas dan reabilitasnya. Kuesioner diujikan pada 25 responden. Hasil: IPAQ versi Indonesia memiliki validitas kriteria yang memuaskan . Sejumlah 7 item pertanyaan dalam IPAQ dinyatakan valid. Nilai Kaiser-Meyer-Olkin sebesar 0,910, dan Bartlettâ€™s test of sphericity sejumlah X2 = 573.434 (df=28 , p0.000 ). Diskusi : IPAQ versi Indonesia valid dan reliabel dapat digunakan untuk mengukur aktivitas fisik masyarakat Indonesia.